Factors Associated with the Occurrence of Anemia in Pregnant Women at the Anutapura Hospital in Palu - Ni Nyoman Elfiyunai; Mulyanti M Tahir; Farlina Farlina (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2019)
Anemia is considered a public health problem because its prevalence is still high. Anemia can give bad consequences to pregnant women such as susceptible to disease, Low Birth Weight (LBW), influence on work ability, even on severe anemia can result in death. The formulation of the problem in this study is whether there is a relationship of parity, maternal age, consumption of Fe tablets, distance of pregnancy and utilization of antenatal care with the incidence of anemia in pregnant women at Anutapura General Hospital, Palu. The purpose of this study was to determine the factors associated with the incidence of maternal mortality in Anutapura General Hospital, Palu. This type of research is an observational study with a cross sectional study approach. The independent variables in this study are parity, age, pregnancy distance, and the use of antenatal care services, the dependent variable is anemia in pregnant women. Data analysis using univariate and bivariate analysis and chi-square and multivariate statistical tests. Sampling using the Purposive sampling method. Samples were 87 respondents.There was a relationship of parity (p = 0.003), maternal age (p = 0.005), pregnancy distance (p = 0.001) and utilization of antenatal services (p = 0.002) with the incidence of anemia in pregnant women at Anutapura General Hospital, Palu. The most dominant factor of Fe tablet consumption where the level of Exp (B) value is 1.594 at 95% CI and lower limit value = 0.585 and upper limit = 4.341 with a significance level = 0.000. related to the incidence of anemia in pregnant women at Anutapura General Hospital, Palu.Advice to hospitals, especially health workers to provide counseling to pregnant women about the importance of antenatal care visits at least 4 times during pregnancy, in order to meet the needs of iron tablets during pregnancy.